Fighting Oxidative Stress with Sulfur: Hydrogen Sulfide in the Renal and Cardiovascular Systems - Joshua J. Scammahorn; Isabel T. N. Nguyen; Eelke M. Bos; Harry Van Goor; Jaap A. Joles (MDPI AG, 2021)
Hydrogen sulfide (H2S) is an essential gaseous signaling molecule. Research on its role in physiological and pathophysiological processes has greatly expanded. Endogenous enzymatic production through the transsulfuration and cysteine catabolism pathways can occur in the kidneys and blood vessels. Furthermore, non-enzymatic pathways are present throughout the body. In the renal and cardiovascular system, H2S plays an important role in maintaining the redox status at safe levels by promoting scavenging of reactive oxygen species (ROS). H2S also modifies cysteine residues on key signaling molecules such as keap1/Nrf2, NFκB, and HIF-1α, thereby promoting anti-oxidant mechanisms. Depletion of H2S is implicated in many age-related and cardiorenal diseases, all having oxidative stress as a major contributor. Current research suggests potential for H2S-based therapies, however, therapeutic interventions have been limited to studies in animal models. Beyond H2S use as direct treatment, it could improve procedures such as transplantation, stem cell therapy, and the safety and efficacy of drugs including NSAIDs and ACE inhibitors. All in all, H2S is a prime subject for further research with potential for clinical use.